Analysis of Implementation the National Health Insurance Program Related to Health Services Based on Resources Aspects in Konawe District - Hasrin, Muhammad; Kamalia, La Ode; Harun, Azis (Waluya The International Science of Health Journal, 2023)
Introduction: The Konawe Regency Government has unilaterally terminated the cooperation program with the Social Security Administrator which has been covering health insurance for the poor in Konawe. The Konawe local government has stopped paying premiums to the Health Insurance Agency for the Konawe community with Family Card holders and the health insurance status of family card holders is unclear until now and Family Card participants are no longer able to use family cards to get health insurance either at the health center or other health facilities. Based on this, the researcher wants to analyze the implementation of the National Health Insurance Program related to health services based on the aspect of resources in Konawe Regency. Method: Types of research is qualitative research using a case study approach. In this study, the researcher acts as the main research instrument. Key informants and regular informants as supporting instruments totaling 12 people. Result: In the interview, it was stated that based on our workload analysis, it was sufficient, including the existing health workers, namely 2 (two) general practitioners, 1 (one) dentist, 40 (forty) nurses, 30 (thirty) midwives, 2 (two) analysts people and 15 (fifteen) public health workers. Conclusion: The availability of health workers in 5 (five) public health center is not sufficient. Of the five health centers that became the object of research, there is still one health center that does not yet have a general practitioner.